2022
DOI: 10.7745/kjssf.2022.55.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Growth Conditions on Saponarin, Water-Soluble Vitamins, and Mineral Content of Barley Sprouts Cultivated in Chamber System

Abstract: Barley sprouts contain various secondary metabolites such as polyphenol, policosanol, and γ-aminobutyric acid (GABA). In particular, saponarin, which accounts for about 72% of polyphenols, is well known for antioxidant, anti-inflammatory, and liver function protection effects. Saponarin is greatly affected by environmental conditions such as light, temperature, and moisture. However, there is a lack of studies about the effect of the microclimatic environment on saponarin content in barley sprouts. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Naringenin is then converted to isovitexin, which is rapidly converted to saponarin by UDP-Glc:flavone-7- O -glycosyltransferase (OGT) . To date, many studies have demonstrated that there is a strong correlation between saponarin content in barley sprouts and light intensity and/or photoperiod, which strongly suggests that light conditions may be important for saponarin production. , Moreover, plant saponarin content can be elevated in response to various abiotic stresses, such as light, temperature, and plasma exposure, and it may also mitigate oxidative stress by acting as an antioxidant. However, since most studies have been conducted in controlled environments, the influence on flavonoid biosynthesis and production by in situ environmental factors remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Naringenin is then converted to isovitexin, which is rapidly converted to saponarin by UDP-Glc:flavone-7- O -glycosyltransferase (OGT) . To date, many studies have demonstrated that there is a strong correlation between saponarin content in barley sprouts and light intensity and/or photoperiod, which strongly suggests that light conditions may be important for saponarin production. , Moreover, plant saponarin content can be elevated in response to various abiotic stresses, such as light, temperature, and plasma exposure, and it may also mitigate oxidative stress by acting as an antioxidant. However, since most studies have been conducted in controlled environments, the influence on flavonoid biosynthesis and production by in situ environmental factors remains unclear.…”
Section: Introductionmentioning
confidence: 99%